HUBUNGAN ANTARA STRES DENGAN STRATEGI KOPING MAHASISWA TAHUN PERTAMA AKADEMI KEPERAWATAN - Uswatun Hasanah (JURNAL WACANA KESEHATAN, 2017)
Students are individuals who are in the process of studying and enrolled is undergoing education at one of the universities. The new student is the status the student holds during his freshman year. Stress experienced by students in the first year gives a negative impact on physical and psychological conditions. This study aims to determine the relationship between stress and coping strategies. The research design used is descriptive correlation. This study uses cross sectional approach that is done sampling at the same time. The statistical test used is Chi Square test. The result of the analysis showed that from 81 students (69.23%) with light stress level, 77 students (95.1%) used adaptive coping strategy and among 36 stressed students there were 30 students (8.3%) with maladaptive coping strategy. The results suggest that there is a relationship between stress and coping strategies. Adaptive coping strategies are needed to be able to modify stress.